-6(t-9)-(t+3)=10

Simple and best practice solution for -6(t-9)-(t+3)=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(t-9)-(t+3)=10 equation:


Simplifying
-6(t + -9) + -1(t + 3) = 10

Reorder the terms:
-6(-9 + t) + -1(t + 3) = 10
(-9 * -6 + t * -6) + -1(t + 3) = 10
(54 + -6t) + -1(t + 3) = 10

Reorder the terms:
54 + -6t + -1(3 + t) = 10
54 + -6t + (3 * -1 + t * -1) = 10
54 + -6t + (-3 + -1t) = 10

Reorder the terms:
54 + -3 + -6t + -1t = 10

Combine like terms: 54 + -3 = 51
51 + -6t + -1t = 10

Combine like terms: -6t + -1t = -7t
51 + -7t = 10

Solving
51 + -7t = 10

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-51' to each side of the equation.
51 + -51 + -7t = 10 + -51

Combine like terms: 51 + -51 = 0
0 + -7t = 10 + -51
-7t = 10 + -51

Combine like terms: 10 + -51 = -41
-7t = -41

Divide each side by '-7'.
t = 5.857142857

Simplifying
t = 5.857142857

See similar equations:

| -20z^2+20z+5= | | -3(3n+2)=6 | | 7x-2=3x+6 | | 20m^2+21m+4= | | 6-2x=2x-6 | | x^2+31x-516=0 | | X^3+2x^2+3x+4=0 | | X^2-7x-120=0 | | 4x^2+76x-805=0 | | (y-4)-(y+9)=6y | | (x-2)(3x-3)= | | 5-9[4-(5y-3)]= | | 2+6(x-9)=1-7(x-6) | | 4x^4=864x | | 170x^2-210x-260=0 | | 170x^2-210y-260=0 | | -7y=6x+42 | | 130x^2+20x-110=0 | | (-6+9i)(7+i)= | | 130x^2+210y-260=0 | | 7x-3y=20 | | 9x+2x=3x+2 | | 25x^2-10x+1= | | 70a^2-95a+30=0 | | 2x^2-14y^2+3xy=0 | | 2u^2-14v^2+3uV=0 | | 3(x-4)=9x-5-6x | | 9r-24r^2+16r^3=0 | | 2m+5n=265 | | (x^3+xy+3y^2)-(10x^3+7xy-5y^2)= | | 3x-21=4x | | -9-4=-11 |

Equations solver categories